2002
DOI: 10.1007/s00018-002-8440-8
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprotein IIb/IIIa antagonists - from bench to practice

Abstract: The central role played by the alphaIIb beta3 receptor in platelet aggregation, and hence in platelet thrombosis, has led to the development of a number of parenteral and oral glycoprotein (GP) IIb/IIIa inhibitors for use in cardiovascular disease states, such as acute coronary syndromes and stroke. The predominant effect of these agents is to inhibit platelet aggregation, although studies of alphaIIb beta3 receptor function and various GP IIb/IIIa inhibitors have demonstrated the potential for these agents to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 157 publications
(124 reference statements)
0
16
0
3
Order By: Relevance
“…GPIIb(CD41) is a megakaryocyte marker whose central role in platelet aggregation makes it a promising target for treatment of thrombosis and cardiovascular disease (5,27). GPIIb functions as a heterodimer with GPIIIa(CD61) and regulates cell adhesion and platelet aggregation by binding fibrinogen and von Willebrand factor (44).…”
mentioning
confidence: 99%
“…GPIIb(CD41) is a megakaryocyte marker whose central role in platelet aggregation makes it a promising target for treatment of thrombosis and cardiovascular disease (5,27). GPIIb functions as a heterodimer with GPIIIa(CD61) and regulates cell adhesion and platelet aggregation by binding fibrinogen and von Willebrand factor (44).…”
mentioning
confidence: 99%
“…Binding of fibrinogen leads to a IIbb3-mediated signaling that results in recruitment of a network of signaling molecules and reorganization of the cytoskeleton, irreversible changes that stabilize the clot. Because of its pivotal role in platelet aggregation, a IIbb3 became the target for the development of antagonists that could be used in the setting of acute arterial vascular occlusion (55).…”
Section: Dipyridamolementioning
confidence: 99%
“…The multicenter randomized clinical trials cited above, involving more than 100,000 patients in evaluation of the clinical efficacy of intravenous aIIbb 3 antagonists, have shown that although these agents have a beneficial effect in very specific circumstances, such as preventing ischemic complications in patients undergoing PCI, their benefits in the medical management of acute coronary syndromes and MI are limited (55).…”
Section: Intravenous a Iibb3 Integrin Antagonistsmentioning
confidence: 99%
“…Abciximab also redistributes from platelet to platelet or vascular cells carrying the vitronectin receptor [10]. An estimated 29% and 13% of GP IIb/IIIa receptors are still occupied by abciximab at 8 and 15 days after completion of infusion [11].…”
Section: Pharmacology Of Abciximabmentioning
confidence: 99%
“…In addition, a part of the secreted GP IIb/IIIa complexes already contain bound fibrinogen from the platelet α -granules, which is only partially blocked by abciximab [14,15]. This may result in the expression of unblocked GP IIb/IIIa receptors at the platelet surface [16].Thus, the consistency of inhibition during infusion of abciximab may become less uniform [11,17].…”
Section: Pharmacology Of Abciximabmentioning
confidence: 99%